Mauritius : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Mauritius. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses key issues related to the economy of Mauritius. In 2015, the economy of Mauritius has grown at moderate rate; inflation is low; and the external position has improved. However, macroeconomic conditions remain stable but the authorities face macrofinancial challenges stemming from the recent collapse of a large financial conglomerate, which affected the real economy, as well as risk exposures and potential spillovers from the massive offshore sector and its sizeable inter-linkages with domestic banking activities. Despite these challenges, the medium-term outlook remains favorable, as economic growth is set to be boosted by continued low fuel prices and the start of important investment programs.